The Obesity Related Gene, FTO, Interacts with APOE, and is Associated with Alzheimer's Disease Risk: A Prospective Cohort Study - Keller, Lina; Xu, Weili; Wang, Hui-Xin; Winblad, Bengt; Fratiglioni, Laura; Graff, Caroline (Journal of Alzheimer's disease, 2011)
The FTO gene has been shown to have a small but robust effect on body mass index (BMI) and to increase the risk for diabetes. Both high BMI and diabetes are vascular risk factors that might play a role in the development of Alzheimer's disease (AD) and dementia. Thus, our aim was to explore the impact of FTO on AD and dementia risk. Nine years of follow-up data was gathered from the Kungsholmen project, a prospective population-based study on 1,003 persons without dementia. Cox-regression models were used to assess the relative risks of developing AD and dementia (DSM-III-R criteria) according to FTO genotypes (rs9939609), taking into account APOE, physical inactivity, BMI, diabetes, and cardiovascular disease (CVD). Compared to carriers of the FTO TT-genotype, AA-carriers had a higher risk for AD (RR 1.58, 95% CI: 1.11–2.24) and for dementia (RR 1.48, 95% CI: 1.09–2.02) after adjustment for age, gender, education, and APOE genotype. This effect remained after additional adjustment for physical inactivity, BMI, diabetes, and CVD. An interaction between FTO and APOE was found, with increased risk for dementia for those carrying both FTO AA and APOE ϵ4. Importantly, the effect of the AA-genotype on dementia/AD risk seems to act mostly through the interaction with APOE ϵ4. Our findings suggest that the FTO AA-genotype increases the risk for dementia, and in particular AD, independently of physical inactivity, BMI, diabetes, and CVD measured at baseline. Our results are in line with the recently reported association between FTO and reduced brain volume in cognitively healthy subjects.